2019
DOI: 10.1002/sctm.19-0013
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Timing and Times for Administration of Atorvastatin-Pretreated Mesenchymal Stem Cells in a Preclinical Model of Acute Myocardial Infarction

Abstract: Our previous studies showed that the combination of atorvastatin (ATV) and single injection of ATV‐pretreated mesenchymal stem cells (MSCs) (ATV‐MSCs) at 1 week post‐acute myocardial infarction (AMI) promoted MSC recruitment and survival. This study aimed to investigate whether the combinatorial therapy of intensive ATV with multiple injections of ATV‐MSCs has greater efficacy at different stages to better define the optimal strategy for MSC therapy in AMI. In order to determine the optimal time window for MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 86 publications
(135 reference statements)
1
26
0
Order By: Relevance
“…For instance, a double injection of human MSCs increased the survival of injected cells and their paracrine effects in a critical limb ischemia mouse model when compared to a single injection containing the same dosage of cells [48]. A study on an acute myocardial infarction rat model also indicated that multiple injections of rat MSCs had greater efficacy than single administration [49]. It is consistent with our results that the expression levels of gpx1 and catalase in ovaries was significantly enhanced in the group treated with a high frequency of ASC-CM injection regardless of their age.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a double injection of human MSCs increased the survival of injected cells and their paracrine effects in a critical limb ischemia mouse model when compared to a single injection containing the same dosage of cells [48]. A study on an acute myocardial infarction rat model also indicated that multiple injections of rat MSCs had greater efficacy than single administration [49]. It is consistent with our results that the expression levels of gpx1 and catalase in ovaries was significantly enhanced in the group treated with a high frequency of ASC-CM injection regardless of their age.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the physiological functions of GDF11 in mesenchymal stromal cells (MSCs), which possess mesenchymal stromal characteristics with classic mesenchymal stromal markers. Recent research showed that MSCs play a critical role in maintaining normal cardiac function, as well as in cardiac remodeling during pathological conditions 4‐6 . However, therapeutic effect on myocardial infarction by MSCs is limited due to the poor survival rate given a hostile microenvironment in an ischemic heart.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation and culture of adult rat bone marrow MSCs were performed as previously described [20]. In brief, bone marrow was harvested from the tibia and femur of Sprague-Dawley rats (60-80g, male) and plated into cell culture flasks with complete medium in an incubator set at 37 °C containing 5%…”
Section: Mscs Isolation Culture and Deliverymentioning
confidence: 99%